The Development Of Android-Based Plane Figure Educational Game Using Unity 2D With Fisher Yates Shuffle Algorithm (A Case Study At Sekolah Dasar Negeri 1 Brobot) - Cinde Yuliga Cinde; Tito Pinandita (Journal of Games, Game Art, and Gamification, 2023)
The development of educational games can be utilized optimally as one of the learning media. The learning activity applied in grade IV at SD Negeri 1 Brobot (Public Elementary School 1 of Brobot) still uses conventional methods, it makes students feel bored especially in plane figure material. This study aims to develop an Android-based plane figure educational game using Unity 2D with Fisher Yates Shuffle to increase students' interest and motivation in learning, especially in plane figure material. This study uses RD (Research and Development) using the ADDIE development model. The ADDIE stage includes Analysis, Design, Development, Implementation, Evaluation. In the validation test of the plane figure educational game, the researcher uses two validators, namely a validator as a media expert and another validator as a material expert. In addition, the plane figure educational game was tested for practicality with the subject of 3 students of grade IV at SD Negeri 1 Brobot, who were categorized as high ability (1 student), another one student in medium ability and the rest one is in low ability. At the implementation stage, the pretest and posttest were tested on 12 students to find out the effectiveness of educational games in increasing student learning. The results obtained in the plane figure educational game are from the media expert validation test getting a percentage of 82.8%, the material expert validation test getting a percentage of 87.5%, and the practicality test getting an average percentage of 82.5%. In the pretest and posttest tests, the average percentage is 27.5% pretest and the posttest score is 40.8 and the learning improvement gets an increase of 48.4%.